Reviews of Books (International review of mission, 1932)
Book reviewed in this article: MUSLIM THEOLOGY: Die dogmatischen Lehren der Anhänger des Islam. Von Abu'l-Hasan Ali ibn Ismail al-Ash'ari. Herausgegeben von H. Ritter. MUSLIM THEOLOGY: Der Islam: Mit Ausschluss des Qor'ans. Von Joseph Schacht. MUSLIM THEOLOGY: Islam und Christentum im Mittelalter: Beiträge zur Geschichte der muslimischen Polemik gegen das Christentum in Arabischer Sprache. Von Erdmann Fritsch. MYSTICISM, EARLY AND RECENT: Studies in Early Mysticism in the Near and Middle East. By Margaret Smith MYSTICISM, EARLY AND RECENT: Bahā'ism, its Origin, History and Teachings. By William McElwee Miller, B.D. Introduction by Robert Speer EVANGELICAL BELIEF AND THE THOUGHT OF TO-DAY: Der Evangelische Glaube und das Denken der Gegenwart: Grundzüge einer christlichen Lebensanschauung. 1. Band. Glaube und Denken. Von Karl Heim. PROTESTANT MISSIONS IN SOUTH AMERICA: The River Plate Republics: A Survey of the Religious, Economic and Social Conditions in Argentina, Paraguay and Uruguay. By W. E. Browning. PROTESTANT MISSIONS IN SOUTH AMERICA: The West Coast Republics of South America: Chile, Peru and Bolivia. By W. E. Browning, John Ritchie and Kenneth G. Grubb. PROTESTANT MISSIONS IN SOUTH AMERICA: The Northern Republics of South America: Ecuador, Colombia and Venezuela. By Kenneth G. Grubb. PROTESTANT MISSIONS IN SOUTH AMERICA: The Lowland Indians of Amazonia: A Survey of the Location and Religious Conditions of the Indians of Colombia, Venezuela, the Guianas, Ecuador, Peru, Brazil and Bolivia. By Kenneth G. Grubb. THE FRONTIER PEOPLES OF INDIA: The Frontier Peoples of India: A Missionary Survey. By Alexander McLeish. MAHATMA GANDHI: Mahatma Gandhi at Work: His own Story continued. Edited by C. F. Andrews. MAHATMA GANDHI: The Dawn of Indian Freedom. By Jack C. Winslow and Verrier Elwin. INDUSTRY AND SOCIAL WELFARE IN INDIA: The Indian Peasant Uprooted: A Study of the Human Machine. By Margaret Read. INDUSTRY AND SOCIAL WELFARE IN INDIA: The Social Settlement as an Educational Factor in India. By Clifford Manshardt REMAKING MAN IN AFRICA: The Remaking of Man in Africa. By J. H. Oldham and B. D. Gibson. MORE FROM DR SCHWEITZER: More from the Primeval Forest. By Albert Schweitzer, D.Theol., D.Med., D.Phil. (Strasbourg). Translated by C. T. Campion.